Resilience in Women Entrepeneur’s Leadership for Sustainable Business - Yurianti, Erni; Nawangsari, Lenny Christina (ARE Publisher, 2024)
Objectives: Social and organizational pressures, which call for resilience to ensure company sustainability, are only a few of the major obstacles that women's leadership frequently faces. The purpose of this study is to investigate the elements that influence women's leadership resilience and how it contributes to sustainable business. Methodology: Purposive sampling, a case study design, and in-depth interviews and observation are the methods used in this qualitative study. We used NVivo 14 software to analyze the data and identify thematic patterns after selecting eight female company executives as informants. Finding: Research findings indicate that a variety of values, such as compassion, dedication, self-assurance, bravery, optimistic thinking, and difficult life events, influence the resilience of female leaders. Strong resilience supports the survival of businesses by enabling female leaders to be more creative and flexible when under duress. Conclusion: These results provide business women with practical advice on how to provide training that upholds resilience's fundamental principles..This study makes a valuable contribution by introducing fresh perspectives not fully explored in previous studies, by explicitly identifying fundamental values that impact resilience and presenting a conceptual framework that links resilience to corporate sustainability.